Transnational everyday lives in the city: revisiting gendered relations and caring practices in the neighbourhoods of Athens - Βαΐου Ντίνα (The Greek Review of Social Research, 2013)
In the context delineated by the neoliberal policies and measures, the paper focuses on one of the least discussed “victims” of the crisis, namely changing practices of care, which engage in different ways migrant and local women who have to devise survival strategies in increasingly dire conditions, “here” (in Athens), “there” (in the places where migrant women come from) and “on the way” (in the trajectories of migration). More specifically, the paper focuses on deficits of care for the elderly as a starting point from which to discuss a whole range of everyday practices which on the one hand redefine gendered relations, while on the other they underline the importance of space and place, on a series of different and nested scales, “from the body to the global system”.